Intermediate accounting - Meigs, Walter B.; Mosich, A. N. (New York : McGraw-Hill, 1978)
The book provides a guide for users of financial information on how to understand and pass exams on accounting. It provides likely examination questions and how students can easily answer them.
usc 14/02/2019
Loans
Keywords: Accounting